We know that,

1. $$ \int_0^1 t^{b-1} (1-t)^{c-b-1} (1-tz)^{-a} dt = \beta(b, c-b) ~\,_2F_1~(a, b, c, z) $$

2. $$ \int_0^1 t^{a-1} (1-t)^{b-1} e^{ct} dt = \beta(a, b) ~\,_1F_1~(a, b, c) $$ where $\beta(\cdot, \cdot)$, $\,_2F_1~(\cdot, \cdot, \cdot, \cdot)$, $~\,_1F_1~(\cdot, \cdot, \cdot)$ are Beta function, Gauss Hypergeometric function and Confluent Hypergeometric function respectively.

Then, how to find the following integrals?

3. $$ \int_0^{\theta} t^{b-1} (1-t)^{c-b-1} (1-tz)^{-a}~dt = ? $$ 4. $$ \int_0^{\theta} t^{a-1} (1-t)^{b-1} e^{ct}~dt = ? $$ where $0 < \theta < 1$.


Fist of all, Welcome to the site !

The first antiderivative is given in terms of the Appell hypergeometric function of two variables $$I=\int t^{b-1} (1-t)^{c-b-1} (1-tz)^{-a}\,dt$$ $$I=t^b \left(\frac{F_1(b;b-c,a;b+1;t,t z)}{b}+\frac{t F_1(b+1;b-c+1,a;b+2;t,t z)}{b+1}\right)$$

The second one seems to be much more problematic (because of the exponential) and I should try a series expansion $$J=\int t^{a-1} (1-t)^{b-1} e^{ct}\,dt= \int t^{a-1} (1-t)^{b-1}\left( \sum_{n=0}^\infty \frac {c^n}{n!} t^n\right)\,dt$$ $$J=\sum_{n=0}^\infty \frac {c^n}{n!}\int t^{n+a-1} (1-t)^{b-1}\,dt=\sum_{n=0}^\infty \frac {c^n}{n!}\,B_t(a+n,b)$$

| cite | improve this answer | |
  • $\begingroup$ Thank you @Claude Leibovici $\endgroup$ – saroja kumar Singh May 24 at 14:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.